Breast cancer survivorship care during the COVID-19 pandemic within an urban New York Hospital System. (October 2021) - Mo, Allen; Chung, Julie; Eichler, Jeremy; Yukelis, Sarah; Feldman, Sheldon; Fox, Jana; Garg, Madhur; Kalnicki, Shalom; Ohri, Nitin; Sparano, Joseph A.; Klein, Jonathan
Abstract: Purpose: To examine clinicodemographic determinants associated with breast cancer survivorship follow-up during COVID-19. Methods: We performed a retrospective, population-based cohort study including early stage (Stage I-II) breast cancer patients who underwent resection between 2006 and 2018 in a New York City hospital system. The primary outcome was oncologic follow-up prior to and during the COVID-19 pandemic. Secondary analyses compared differences in follow-up by COVID-19 case rates stratified by ZIP code. Results: A total of 2942 patients with early-stage breast cancer were available for analysis. 1588 (54%) of patients had attended follow-up in the year prior to the COVID-19 period but failed to continue to follow-up during the pandemic, either in-person or via telemedicine. 1242 (42%) patients attended a follow-up appointment during the COVID-19 pandemic. Compared with patients who did not present for follow-up during COVID-19, patients who continued their oncologic follow-up during the pandemic were younger ( p  = 0.049) more likely to have received adjuvant radiation therapy ( p  = 0.025), and have lower household income ( p  = 0.031) on multivariate modeling. When patients who live in Bronx, New York, were stratified by ZIP code, there was a modest negative association (r = −0.56) between COVID-19 cases and proportion of patients who continued to follow-up during the COVID-19 period. Conclusion: We observed a dramatic disruption in routine breast cancer follow-up during the COVID-19 pandemic. Providers and health systems should emphasize reintegrating patients who missed appointments during COVID-19 back into regular surveillance programs to avoid significant morbidity and mortality from missed breast cancer recurrences. Highlights: A dramatic disruption in routine oncologic follow-up was observed during the COVID-19 period. Over half of patients with breast cancer at our center did not attend routine oncologic follow-up during COVID-19. Patients who were younger, had lower SES, and who received radiotherapy were more likely to follow-up during the pandemic. A modest negative association was observed between local ZIP code COVID-19 infection rates and follow-up attendance rate.